Adhesive sheet for temporary fixing of electronic component

By introducing the light and thermal conversion layer containing charcoal black in the fixed adhesive/adhesive sheet of electronic components, using the solid resin composition and specific additives to solve the difficulty and insufficient heat resistance of the material management of the adhesive/adhesive sheet The problem achieves the effect of excellent heat resistance and applicable to semiconductor purposes.

CN119365961APending Publication Date: 2025-01-24NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380046946.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-02
Filing Date
2023-06-06
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The adhesive/adhesive sheet for temporary fixing of existing electronic components has the problem of sedimentation of carbon black powder dispersion of photothermal conversion materials, which leads to difficulty in material management, and the black printing layer has insufficient heat resistance and chemical liquid resistance characteristics, so it cannot be applied. For semiconductor use.

Method used

An adhesive/adhesive sheet for fixing electronic components containing a carbon black photothermal conversion layer composed of a curable resin composition containing pentaerythritol-based polyfunctional (meth)acrylate and benzene was developed. Ethylene thermoplastic elastomer has excellent heat resistance and chemical liquid resistance, and exhibits peelability under different wavelengths of light.

Benefits of technology

It has realized a temporary bonding/adhesive sheet with optical conversion function and excellent thermal resistance, which solves the problem of difficulty management difficulties and heat resistance, and is suitable for semiconductor packaging and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365961A_ABST
    Figure CN119365961A_ABST
Patent Text Reader

Abstract

Provided is an adhesive / adhesive sheet for temporary fixing of an electronic component, which has a photothermal conversion function and excellent heat resistance. An adhesive / adhesive sheet for fixing an electronic component according to an embodiment of the present invention is provided with a photothermal conversion layer, the adhesive / adhesive sheet for fixing an electronic component having a transmittance of light having a wavelength of 1032 nm of 60% or less and a transmittance of light having a wavelength of 355 nm of 60% or less, the photothermal conversion layer containing carbon black, and the photothermal conversion layer containing carbon black. The photothermal conversion layer has a 5% weight loss temperature of 300 DEG C or more after ultraviolet irradiation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet for temporarily fixing electronic parts. Background Art

[0002] In recent years, in order to improve the characteristics of semiconductor devices, the trend of fixing semiconductor chips and sealed resin substrates on hard supporting substrates to implement high-temperature processes has accelerated, centered on fields such as semiconductor packaging. For example, in the RDL formation process for forming circuits on semiconductor packages sealed with black resin, a method of temporarily fixing the processed body flatly on a translucent substrate such as glass and separating the hard substrate after forming the RDL on the processed body has been studied. In such applications, liquid adhesives containing carbon black powder as photothermal conversion materials are widely used. In the technology using photothermal conversion materials, the photothermal conversion material is applied to a translucent substrate to form a photothermal conversion layer, and the processed body is firmly fixed during processing. When peeling, the photothermal conversion layer absorbs the light and converts it into heat to undergo thermal decomposition by laser irradiation of a specified wavelength, thereby making it possible to simply separate the processed body from the translucent substrate (laser debonding). However, most of the above-mentioned liquid adhesives as photothermal conversion materials are added with carbon black powder and fillers, which cause sedimentation of the dispersion over time, so there is a problem of difficulty in material management during manufacturing. As a method for solving such problems, a technology of using a general-purpose black printing substrate formed of a material containing carbon black to form a film to make a double-sided tape has been studied. However, there is a problem that the black printing layer has poor heat resistance and chemical liquid resistance and is not suitable for semiconductor applications.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 4565804

[0006] Patent Document 2: Japanese Patent No. 4405246 Summary of the invention

[0007] Problems to be solved by the invention

[0008] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a pressure-sensitive adhesive sheet for temporarily fixing electronic components which has a light-to-heat conversion function and is excellent in heat resistance.

[0009] Means used to solve problems

[0010] [1] An electronic component fixing adhesive / adhesive sheet according to an embodiment of the present invention comprises a light-to-heat conversion layer, wherein the transmittance of light of a wavelength of 1032 nm of the electronic component fixing adhesive / adhesive sheet is 60% or less, the transmittance of light of a wavelength of 355 nm of the electronic component fixing adhesive / adhesive sheet is 60% or less, the light-to-heat conversion layer contains carbon black, and the 5% weight loss temperature of the light-to-heat conversion layer after ultraviolet irradiation is 300° C. or more.

[0011] [2] In the pressure-sensitive adhesive sheet for fixing electronic components described in [1] above, the light-to-heat conversion layer may be composed of a curable resin composition.

[0012] [3] In the pressure-sensitive adhesive sheet for fixing electronic components described in [2] above, the light-to-heat conversion layer may contain a photopolymerization initiator.

[0013] [4] In the pressure-sensitive adhesive or adhesive sheet for fixing electronic components described in [3] above, the curable resin composition may contain a pentaerythritol-based multifunctional (meth)acrylate.

[0014] [5] In the pressure-sensitive adhesive sheet for fixing electronic components described in [1] above, the light-to-heat conversion layer may contain a styrene-based thermoplastic elastomer.

[0015] [6] The pressure-sensitive adhesive sheet for fixing electronic components according to any one of [1] to [5] may further include a substrate, and the light-to-heat conversion layer may be disposed on at least one side of the substrate.

[0016] Effects of the Invention

[0017] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet for temporarily fixing electronic components which has a light-to-heat conversion function and is excellent in heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic cross-sectional view of a pressure-sensitive adhesive sheet for temporarily fixing electronic components according to one embodiment of the present invention. DETAILED DESCRIPTION

[0019] A. Overview of adhesive / adhesive sheets for temporary fixing of electronic components

[0020] Figure 1 1 is a schematic cross-sectional view of an adhesive / adhesive sheet for temporarily fixing electronic components according to an embodiment of the present invention. The adhesive / adhesive sheet 110 for temporarily fixing electronic components includes a light-to-heat conversion layer 10. Figure 1As shown in (b), the adhesive / adhesive sheet 110' for electronic components may further include a substrate 20. In one embodiment, a light-to-heat conversion layer 10 is arranged on at least one side of the substrate 20. In one embodiment, the adhesive / adhesive sheet 110" for electronic components further includes an adhesive layer 30. For example, the light-to-heat conversion layer 10, the substrate 20, and the adhesive layer 30 are arranged in sequence. The substrate 20 may also be omitted. In addition, although not shown in the figure, the adhesive / adhesive sheet for fixing electronic components may include any appropriate other layers as needed. It should be noted that in this specification, the "adhesive / adhesive sheet" is a concept that includes adhesive sheets and adhesive sheets. Hereinafter, the adhesive / adhesive sheet for fixing electronic components is sometimes referred to as an adhesive / adhesive sheet.

[0021] The above-mentioned photothermal conversion layer is a layer that absorbs light of a specified wavelength and converts the light into heat. Due to the heat generated by the photothermal conversion layer, the photothermal conversion layer itself decomposes, or the layer adjacent to the photothermal conversion layer decomposes thermally. As a result, the adhesive / adhesive sheet for temporary fixing of electronic components shows peelability. In one embodiment, the photothermal conversion layer has adhesiveness or viscosity before absorbing light of a specified wavelength. By absorbing light of a specified wavelength, the surface shape of the photothermal conversion layer changes, thereby showing peelability. In addition, due to the heat generated by the photothermal conversion layer, any layer constituting the adhesive / adhesive sheet can be thermally decomposed to generate gas. As a result, the surface shape of the adhesive / adhesive sheet changes, thereby showing peelability. It should be noted that in this specification, "thermal decomposition" means that a weight loss of 5% or more can be produced by heating at 250°C or above (preferably 300°C or above).

[0022] The light-to-heat conversion layer contains carbon black. In the light-to-heat conversion layer, the carbon black absorbs light of a predetermined wavelength, thereby exhibiting the light-to-heat conversion effect. The light-to-heat conversion layer containing carbon black can be applied to an adhesive / adhesive sheet in a film form, which is advantageous in that material management becomes easier than using a liquid light-to-heat conversion material. In addition, it is also advantageous in that a structure having excellent heat resistance and chemical liquid resistance can be formed.

[0023] The transmittance of light of a wavelength of 1032nm of the above-mentioned adhesive / adhesive sheet is 60% or less. If within such a range, an adhesive / adhesive sheet that preferably exhibits a photothermal conversion effect can be obtained. The transmittance of light of a wavelength of 1032nm of the adhesive / adhesive sheet is preferably 55% or less, more preferably 50% or less, further preferably 40% or less, and particularly preferably 30% or less. If within such a range, an adhesive / adhesive sheet with excellent releasability based on IR laser can be obtained. In one embodiment, the transmittance of light of a wavelength of 1032nm of the adhesive / adhesive sheet is 10% or more. In another embodiment, the transmittance of light of a wavelength of 1032nm of the adhesive / adhesive sheet is 0% to 5%, 0% to 2% or 0%.

[0024] The transmittance of light of a wavelength of 355nm of the above-mentioned adhesive / adhesive sheet is 60% or less. If it is within such a range, an adhesive / adhesive sheet that preferably exhibits a photothermal conversion effect can be obtained. The transmittance of light of a wavelength of 355nm of the adhesive / adhesive sheet is preferably 50% or less, more preferably 45% or less, and further preferably 40% or less. If it is within such a range, an adhesive / adhesive sheet with excellent releasability based on UV laser can be obtained. In one embodiment, the transmittance of light of a wavelength of 355nm of the adhesive / adhesive sheet is 10% or more. In another embodiment, the transmittance of light of a wavelength of 355nm of the adhesive / adhesive sheet is 0% to 5%, 0% to 2% or 0%.

[0025] According to the present invention, by forming a photothermal conversion layer containing carbon black and configuring it in a manner such that the transmittance of light with a wavelength of 1032 nm is less than 60% and the transmittance of light with a wavelength of 355 nm is less than 60%, it is possible to produce peeling properties using either infrared light or ultraviolet light, thereby obtaining an adhesive / adhesive sheet for temporarily fixing electronic components having a wide range of choices for irradiated light.

[0026] The above-mentioned light-to-heat conversion layer was subjected to a cumulative light intensity of 1380 mJ / cm 2 The 5% weight loss temperature of the photothermal conversion layer after irradiation with light of a wavelength of 365nm is above 300°C. If it is within such a range, a photothermal conversion layer with excellent heat resistance can be obtained. The 5% weight loss temperature refers to the temperature at which the weight of the sample to be evaluated is reduced by 5 weight% relative to the dry weight of the sample before heating when the temperature of the sample is increased. The 5% weight loss temperature is measured using a differential thermal analyzer under the measurement conditions of a heating temperature of 10°C / min, a nitrogen atmosphere, and a flow rate of 25ml / min. The dry weight of the sample refers to the weight excluding the water content in the sample. Hereinafter, in this specification, the photothermal conversion layer is sometimes measured with a cumulative light amount of 1380mJ / cm 2 The 5% weight loss temperature after irradiation with light of a wavelength of 365 nm is referred to as the "5% weight loss temperature after ultraviolet irradiation".

[0027] The initial (normal) adhesion of the above-mentioned adhesive / adhesive sheet at 23°C when the light-to-heat conversion layer is attached to PET is preferably 0.2N / 20mm~10N / 20mm, and more preferably 3N / 20mm~8N / 20mm. If it is within such a range, an adhesive / adhesive sheet suitable for temporary fixing purposes without positional offset on the support body can be obtained. The initial adhesion is the adhesion before the peeling property based on light absorption is exhibited. The adhesion is measured in accordance with JIS Z 0237:2000. Specifically, the light-to-heat conversion layer is attached to a glass plate (arithmetic mean surface roughness Ra: 10nm±8nm) by making a 2kg roller go back and forth once, and then the adhesive / adhesive sheet is peeled off at a peeling angle of 180° and a peeling speed (pulling speed) of 300mm / min for measurement.

[0028] The initial (normal) adhesive force of the adhesive / adhesive sheet at 23°C when the light-to-heat conversion layer is attached to the glass plate is preferably 0.20 N / 20 mm to 10 N / 20 mm, more preferably 1 N / 20 mm to 7 N / 20 mm, and further preferably 2 N / 20 mm to 5 N / 20 mm. If it is within this range, an adhesive / adhesive sheet suitable for temporary fixing purposes without positional deviation on the support can be obtained.

[0029] In one embodiment, the light-to-heat conversion layer is attached to a glass plate to accumulate light of 1380 mJ / cm 2 The adhesive strength after ultraviolet irradiation at 23°C after irradiation with light of a wavelength of 365 nm is preferably 0.01 N / 20 mm to 3 N / 20 mm, and more preferably 0.04 N / 20 mm to 2 N / 20 mm. Within this range, an adhesive / adhesive sheet having excellent releasability can be obtained. The ultraviolet irradiation can be performed, for example, from one side of the glass plate.

[0030] The thickness of the pressure-sensitive adhesive sheet for temporarily fixing electronic components is preferably 10 μm to 500 μm, more preferably 20 μm to 400 μm.

[0031] In one embodiment, the above-mentioned adhesive / adhesive sheet is used in a manner that one side (the light-to-heat conversion layer side) is adhered to a support (e.g., carrier glass) and an electronic component (e.g., a semiconductor component such as a semiconductor wafer) is arranged on the other side. In the present invention, if the adhesive / adhesive sheet of the present invention is used, the electronic component can be easily separated from the support by the above-mentioned action of the light-to-heat conversion layer. In addition, the electronic component can be arranged on the light-to-heat conversion layer side to fix and peel off the electronic component.

[0032] B. Light-to-heat conversion layer

[0033] In one embodiment, the photothermal conversion layer is a layer that can be thermally decomposed and generate gas by applying heat. The applied heat can be heat caused by the heat of the photothermal conversion layer, or heat caused by the heat of a layer different from the photothermal conversion layer constituting the adhesive / adhesive sheet (for example, a substrate). It should be noted that in this specification, the characteristics "after ultraviolet irradiation" are sometimes specified, but please note that such a specification does not specifically specify whether the photothermal conversion layer changes in characteristics due to ultraviolet irradiation. The photothermal conversion layer can be a layer whose characteristics change (for example, curing) by ultraviolet irradiation, or a layer whose characteristics do not change due to ultraviolet irradiation.

[0034] In one embodiment, the photothermal conversion layer is a layer capable of absorbing near infrared rays. In more detail, the transmittance of light of a wavelength of 1032 nm of the above-mentioned photothermal conversion layer is preferably 60% or less, more preferably 55% or less, more preferably 50% or less, further preferably 40% or less, and particularly preferably 30% or less. If it is within such a range, a photothermal conversion layer that easily and preferably absorbs IR laser and generates heat can be formed. In one embodiment, the transmittance of light of a wavelength of 1032 nm of the photothermal conversion layer is 5% or more.

[0035] In one embodiment, the light-to-heat conversion layer is a layer capable of absorbing ultraviolet rays. In one embodiment, the light-to-heat conversion layer has a transmittance of light at a wavelength of 355 nm of preferably 60% or less, more preferably 50% or less, more preferably 45% or less, and further preferably 40% or less. In one embodiment, the light-to-heat conversion layer has a transmittance of light at a wavelength of 355 nm of 1% or more.

[0036] The thickness of the light-to-heat conversion layer is preferably 1 μm to 100 μm, more preferably 2 μm to 50 μm, further preferably 3 μm to 30 μm, and particularly preferably 5 μm to 20 μm.

[0037] As described above, the 5% weight loss temperature of the above-mentioned photothermal conversion layer after ultraviolet irradiation is above 300°C. The 5% weight loss temperature of the above-mentioned photothermal conversion layer after ultraviolet irradiation is preferably 310°C to 400°C, more preferably 320°C to 380°C, and particularly preferably 330°C to 370°C. If it is within such a range, an adhesive / adhesive sheet with excellent heat resistance can be obtained. In addition, the RDL formation process is usually carried out at a temperature below 250°C. Therefore, if the 5% weight loss temperature after ultraviolet irradiation is within the above range, the outgassing from the photothermal conversion layer in the RDL formation process is reduced, which can reduce the impact on electronic components and achieve a stable process.

[0038] The above-mentioned light-to-heat conversion layer was subjected to a cumulative light intensity of 1380 mJ / cm 2The elastic modulus of the photothermal conversion layer based on the nanoindentation method after irradiation with light of a wavelength of 365nm (also referred to as the elastic modulus after ultraviolet irradiation) is preferably 1MPa or more, more preferably 50MPa to 5GPa, and further preferably 200MPa to 3GPa. If it is within such a range, the shape of the photothermal conversion layer preferably changes during laser irradiation, and excellent peelability can be exhibited. In one embodiment, the elastic modulus of the photothermal conversion layer after ultraviolet irradiation based on the nanoindentation method is 200MPa or more (preferably 300MPa or more, more preferably 500MPa or more). If it is within such a range, a photothermal conversion layer with particularly excellent heat resistance and chemical resistance can be formed. The elastic modulus based on the nanoindentation method refers to the elastic modulus obtained by continuously measuring the load and the penetration depth of the indenter when the indenter is pressed into the sample during loading and unloading, and the load-indentation depth curve obtained. The elastic modulus based on the nanoindentation method is obtained by numerically processing the displacement-load hysteresis curve obtained by pressing a diamond Berkovich-type (triangular pyramid-type) probe vertically on the surface of the measured object using the software (triboscan) attached to the measuring device. In this specification, the elastic modulus based on the nanoindentation method refers to the elastic modulus measured under the measurement conditions of a single indentation method at a specified temperature (25°C) using a nanoindenter (Triboindenter TI-950 manufactured by Hysitron) at an indentation speed of about 500nm / second, a pull-out speed of about 500nm / second, and an indentation depth of about 100nm. It should be noted that the elastic modulus of the photothermal conversion layer after ultraviolet irradiation can be adjusted by the type of material contained in the layer, the structure of the base polymer constituting the material, the type / amount of additives added to the layer, etc.

[0039] The above-mentioned light-to-heat conversion layer was subjected to a cumulative light intensity of 1380 mJ / cm 2 The tensile elastic modulus of the photothermal conversion layer after irradiation with light of a wavelength of 365 nm is preferably 0.1 MPa or more, more preferably 5 MPa to 5 GPa, and further preferably 20 MPa to 3 GPa. If it is within such a range, the shape of the photothermal conversion layer preferably changes during laser irradiation, and excellent peelability can be exhibited. In one embodiment, the photothermal conversion layer is subjected to a cumulative light dose of 1380 mJ / cm 2 The tensile elastic modulus of the light-to-heat conversion layer after irradiation with light having a wavelength of 365 nm is 20 MPa or more (preferably 30 MPa or more, more preferably 50 MPa or more). The method for measuring the tensile elastic modulus is described below.

[0040] As described above, the light-to-heat conversion layer contains carbon black. Typically, the light-to-heat conversion layer is formed of any appropriate resin and can be constituted by containing carbon black in the resin.

[0041] The content of carbon black is preferably 1 to 50 parts by weight, more preferably 3 to 40 parts by weight, and further preferably 5 to 30 parts by weight relative to 100 parts by weight of the resin. Within this range, a light-to-heat conversion layer that can preferably exhibit a light-to-heat conversion function and has excellent mechanical strength can be formed.

[0042] Any appropriate resin may be used as the resin constituting the light-to-heat conversion layer, and examples of the resin constituting the light-to-heat conversion layer include acrylic resins, epoxy resins, polyester resins, polystyrene resins, polyimide resins, and polyurethane resins. Among them, acrylic resins are preferred.

[0043] The light-to-heat conversion layer may be formed of a curable resin composition (curable adhesive) or a pressure-sensitive adhesive. Examples of the pressure-sensitive adhesive include acrylic adhesives, silicone adhesives, epoxy adhesives, styrene thermoplastic elastomers, and ester adhesives. Preferably, styrene thermoplastic elastomers are used.

[0044] Preferably, the above-mentioned light-to-heat conversion layer is composed of a curable (e.g., active energy ray curable or thermosetting) resin composition, more preferably composed of a cured product of an active energy ray curable resin composition, and more preferably composed of a cured product of an acrylic active energy ray curable resin composition. The light-to-heat conversion layer formed by a cured product of a curable resin composition is advantageous in terms of excellent heat resistance. In one embodiment, the light-to-heat conversion layer formed in the form of a cured product of a curable resin composition contains a polymerization initiator. The polymerization initiator is, for example, a photopolymerization initiator or a thermal polymerization initiator. Preferably, the light-to-heat conversion layer composed of a curable resin composition contains a photopolymerization initiator. The above-mentioned near-infrared absorber may be contained in a curable resin composition. In one embodiment, the curable resin composition contains a pentaerythritol-based multifunctional (meth)acrylate. If a pentaerythritol-based multifunctional (meth)acrylate is used, a light-to-heat conversion layer with excellent heat resistance can be formed.

[0045] In one embodiment, as the above-mentioned active energy ray-curable resin composition, an active energy ray-curable resin composition (A1) containing a base polymer as a matrix (or a monomer or oligomer constituting the base polymer) and an active energy ray-reactive compound (monomer or oligomer) is used. In another embodiment, an active energy ray-curable resin composition (A2) containing an active energy ray-reactive polymer as a base polymer is used. In one embodiment, the above-mentioned base polymer has a functional group that can be cleaved by a photopolymerization initiator. As the functional group, for example, a functional group having a carbon-carbon double bond can be listed. As active energy rays, for example, γ rays, ultraviolet rays, visible light, infrared rays (heat rays), radio waves, α rays, β rays, electron rays, plasma flows, ionizing rays, particle beams, etc. are listed. Preferably, ultraviolet rays are used.

[0046] Examples of the base polymer used in the resin composition (A1) include rubber polymers such as natural rubber, polyisobutylene rubber, styrene-butadiene rubber, styrene-isoprene-styrene block copolymer rubber, recycled rubber, butyl rubber, polyisobutylene rubber, nitrile rubber (NBR), etc.; silicone polymers; acrylic polymers, etc. These polymers may be used alone or in combination of two or more. Among them, acrylic polymers are preferred.

[0047] Examples of the acrylic polymer include homopolymers or copolymers of (meth)acrylates such as alkyl (meth)acrylates, cycloalkyl (meth)acrylates, and aryl (meth)acrylates; and copolymers of the (meth)acrylates and other copolymerizable monomers. Specific examples of the alkyl (meth)acrylate include C1-20 alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among them, alkyl (meth)acrylates having a linear or branched alkyl group having 4 to 18 carbon atoms can be preferably used.

[0048] As the above-mentioned other copolymerizable monomers, for example, functional group-containing monomers such as carboxyl group-containing monomers, acid anhydride monomers, hydroxyl group-containing monomers, glycidyl group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, acrylamide and acrylonitrile can be listed. As carboxyl group-containing monomers, for example, acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid and crotonic acid can be listed. As anhydride monomers, for example, maleic anhydride and itaconic anhydride can be listed. As hydroxyl group-containing monomers, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate can be listed. As the monomer containing glycidyl group, for example, (meth) glycidyl acrylate and (meth) methyl glycidyl acrylate can be cited. As the monomer containing sulfonic acid group, for example, styrene sulfonic acid, allyl sulfonic acid, 2-(meth) acrylamido-2-methylpropanesulfonic acid, (meth) acrylamidopropanesulfonic acid, (meth) sulfopropyl acrylate and (meth) acryloxynaphthalenesulfonic acid can be cited. As the monomer containing phosphoric acid group, for example, 2-hydroxyethyl acryloyl phosphate can be cited. As acrylamide, for example, N-acryloyl morpholine can be cited. They can be used alone or in combination of two or more. The content ratio of the structural unit derived from the above-mentioned copolymerizable monomer is preferably 60 parts by weight or less, and more preferably 40 parts by weight or less, relative to 100 parts by weight of the base polymer (acrylic polymer).

[0049] In one embodiment, an acrylic monomer having a glass transition temperature of 40°C or more when forming a homopolymer is used as a monomer constituting an acrylic polymer. That is, the acrylic polymer contains a structural unit derived from an acrylic monomer having a glass transition temperature of 40°C or more when forming a homopolymer. As such acrylic monomers, methyl methacrylate, glycidyl methacrylate, isobutyl methacrylate, acrylonitrile, methacrylonitrile, isopropyl acrylamide, acryloyl morpholine, isobornyl acrylate, etc. can be cited. Among them, methyl methacrylate is preferred. If an acrylic polymer containing a structural unit derived from such a monomer is used, stickiness caused by decomposition products caused by laser irradiation can be prevented. The content ratio of the structural unit derived from the acrylic monomer having a glass transition temperature of 40°C or more when forming a homopolymer is preferably 30 to 80 parts by weight, and more preferably 40 to 75 parts by weight, relative to 100 parts by weight of the base polymer (acrylic polymer). If within such a range, the above effect becomes significant.

[0050] The acrylic polymer may include a structural unit derived from a multifunctional monomer. If a multifunctional monomer is used, a light-to-heat conversion layer with excellent heat resistance can be formed. As a multifunctional monomer, for example, hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy (meth)acrylate (ie, polyglycidyl (meth)acrylate), polyester (meth)acrylate and carbamate (meth)acrylate. They can be used alone or in combination of two or more. In the case of a structural unit derived from a multifunctional monomer, the content ratio of the structural unit derived from the above-mentioned multifunctional monomer is preferably 30 parts by weight or more, and more preferably 40 parts by weight or more, relative to 100 parts by weight of the base polymer (acrylic polymer). The upper limit of the content of the structural unit derived from the polyfunctional monomer is preferably 400 parts by weight or less, more preferably 300 parts by weight or less, based on 100 parts by weight of the base polymer (acrylic polymer).

[0051] The weight average molecular weight of the acrylic polymer is preferably 10,000 to 1,500,000, and more preferably 20,000 to 1,000,000. The weight average molecular weight can be measured by GPC (solvent: THF).

[0052] Examples of the active energy ray reactive compound that can be used in the resin composition (A1) include photoreactive monomers or oligomers having a functional group having a polymerizable carbon-carbon multiple bond, such as an acryloyl group, a methacryloyl group, a vinyl group, an allyl group, an ethynyl group, etc. Specific examples of the photoreactive monomer include esters of (meth)acrylic acid and a polyol, such as trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxy penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, and polyethylene glycol di(meth)acrylate; polyfunctional urethane (meth)acrylate; epoxy (meth)acrylate; and oligoester (meth)acrylate. In addition, monomers such as methacryloyl isocyanate, 2-methacryloyloxyethyl isocyanate (2-isocyanatoethyl methacrylate), and m-isopropenyl-α,α-dimethylbenzyl isocyanate may also be used. Specific examples of the photoreactive oligomer include dimers to pentamers of the above monomers. The molecular weight of the photoreactive oligomer is preferably 100 to 3,000.

[0053] In one embodiment, the active energy ray-curable resin composition (A1) contains a pentaerythritol-based multifunctional (meth)acrylate as the active energy ray-reactive compound. The pentaerythritol-based multifunctional (meth)acrylate can be obtained by esterifying a part or all of the hydroxyl groups of pentaerythritol or a polymer thereof with a (meth)acrylate. If a pentaerythritol-based multifunctional (meth)acrylate is used as the active energy ray-reactive compound, a light-to-heat conversion layer having excellent heat resistance can be formed.

[0054] As the active energy ray-reactive compound, a monomer such as epoxidized butadiene, glycidyl methacrylate, acrylamide, vinylsiloxane, or an oligomer composed of the monomer can be used.

[0055] In the resin composition (A1), the active energy ray-reactive compound is contained in an amount of preferably 0.1 to 500 parts by weight, more preferably 5 to 300 parts by weight, and even more preferably 40 to 200 parts by weight, based on 100 parts by weight of the base polymer.

[0056] Examples of the active energy ray-reactive polymer (base polymer) contained in the resin composition (A2) include polymers having functional groups having carbon-carbon multiple bonds, such as acryloyl, methacryloyl, vinyl, allyl, and ethynyl groups. Specific examples of the active energy ray-reactive polymer include polymers composed of polyfunctional (meth)acrylates (for example, polymers containing structural units derived from polyfunctional monomers), photocationic polymerizable polymers, polymers containing cinnamoyl groups, such as polyvinyl cinnamate, diazotized aminophenol novolac resins, and polyacrylamide.

[0057] In one embodiment, an active energy ray reactive polymer is used which is formed by introducing active energy ray polymerizable carbon-carbon multiple bonds into the side chain, main chain and / or main chain terminal of the acrylic polymer. As a method for introducing radiation polymerizable carbon-carbon double bonds into the acrylic polymer, for example, a method of copolymerizing raw material monomers including a monomer having a predetermined functional group (first functional group) to obtain an acrylic polymer, and then subjecting a compound having a predetermined functional group (second functional group) capable of reacting with the first functional group and a radiation polymerizable carbon-carbon double bond to a condensation reaction or an addition reaction with the acrylic polymer while maintaining the radiation polymerizability of the carbon-carbon double bond.

[0058] As a combination of the first functional group and the second functional group, for example, carboxyl and epoxy, epoxy and carboxyl, carboxyl and aziridine, aziridine and carboxyl, hydroxyl and isocyanate, isocyanate and hydroxyl can be cited. Among these combinations, from the perspective of the ease of reaction tracking, the combination of hydroxyl and isocyanate, the combination of isocyanate and hydroxyl is preferred. In addition, when the technical difficulty of making a polymer with a highly reactive isocyanate group is high, from the perspective of the ease of making or obtaining an acrylic polymer, it is more preferred that the first functional group on the acrylic polymer side is a hydroxyl group and the second functional group is an isocyanate. In this case, as an isocyanate compound having both a radiation-polymerizable carbon-carbon double bond and an isocyanate group as a second functional group, for example, methacryloyl isocyanate, 2-methacryloyloxyethyl isocyanate, and m-isopropenyl-α,α-dimethylbenzyl isocyanate can be cited. In addition, as the acrylic polymer having a first functional group, an acrylic polymer containing a structural unit derived from the above-mentioned hydroxyl-containing monomer is preferred, and an acrylic polymer containing a structural unit derived from an ether compound such as 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether is also preferred.

[0059] The resin composition (A2) may further contain the active energy ray-reactive compound (monomer or oligomer).

[0060] In one embodiment, the active energy ray-curable resin composition includes a polymerization initiator. As the polymerization initiator, for example, a photopolymerization initiator or a thermal polymerization initiator can be used, and a photopolymerization initiator is preferred.

[0061] As the photopolymerization initiator, any appropriate initiator can be used. Examples of the photopolymerization initiator include: α-ketoalcohol compounds such as 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, and 1-hydroxycyclohexylphenylketone; acetophenone compounds such as methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, and 2-methyl-1-[4-(methylthio)-phenyl]-2-morpholinopropane-1-one; benzoin ether compounds such as benzoin ethyl ether, benzoin isopropyl ether, and anisole methyl ether; and benzyl dimethyl ether. Ketal compounds such as ketal; aromatic sulfonyl chloride compounds such as 2-naphthalenesulfonyl chloride; photoactive oxime compounds such as 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime; benzophenone compounds such as benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone; camphorquinone; halogenated ketones; acylphosphine oxides; acylphosphonates, etc. The amount of the photopolymerization initiator used can be set to any appropriate amount.

[0062] In one embodiment, the active energy ray-curable resin composition may include a photosensitizer.

[0064] It is preferred that the active energy ray-curable resin composition contains a crosslinking agent. Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, Azoline crosslinking agents, aziridine crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, amine crosslinking agents, etc.

[0065] The content of the cross-linking agent is preferably 0.01 to 20 parts by weight relative to 100 parts by weight of the base polymer of the resin composition.

[0066] In one embodiment, an epoxy crosslinking agent is preferably used. If an epoxy crosslinking agent is used, a light-to-heat conversion layer having a high 5% weight loss temperature after ultraviolet irradiation can be formed. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1500NP"), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 70P"), polyethylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name "EPIOLIGHT 1500NP"), and polyoxyethylene glycol diglycidyl ether. E-400”), polypropylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name “EPIOL P-200”), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “DENACOL EX-611”), glycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “DENACOL EX-314”), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “DENACOL EX-512”), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, tris(2-hydroxyethyl)isocyanurate triglycidyl, resorcinol diglycidyl ether, bisphenol S diglycidyl ether, epoxy resins having two or more epoxy groups in the molecule, etc. The content of the epoxy crosslinking agent can be set to any appropriate amount according to the desired characteristics, and is typically 0.01 to 10 parts by weight, more preferably 0.05 to 7 parts by weight, relative to 100 parts by weight of the base polymer.

[0067] In one embodiment, an isocyanate crosslinking agent is preferably used. Specific examples of the above-mentioned isocyanate crosslinking agent include: low-order aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate HL"), isocyanurate form of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "Coronate HX") and other isocyanate adducts, etc. The content of the isocyanate crosslinking agent can be set to any appropriate amount according to the desired properties, and is typically 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, relative to 100 parts by weight of the base polymer.

[0068] The active energy ray-curable resin composition may further contain any appropriate additives as required. Examples of the additives include active energy ray polymerization accelerators, free radical scavengers, tackifiers, plasticizers (e.g., trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers, etc.), pigments, dyes, fillers, anti-aging agents, conductive materials, antistatic agents, ultraviolet absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, etc.

[0069] C. Substrate

[0070] The substrate may be made of any appropriate resin, such as polyethylene resin, polypropylene resin, polybutene resin, polymethylpentene resin and other polyolefin resins, polyurethane resin, polyester resin, polyimide resin, polyetheretherketone resin, polystyrene resin, polyvinyl chloride resin, polyvinylidene chloride resin, fluorine-containing resin, silicone resin, cellulose resin, ionomer resin, etc.

[0071] In one embodiment, the substrate is composed of a polyimide resin, a polyester resin or a polyetheretherketone resin. Among them, a polyimide resin is preferred. These resins have UV absorption properties, and if used, the range of choices for the type of laser used in the stripping operation is widened.

[0072] The thickness of the substrate is preferably 2 μm to 300 μm, more preferably 2 μm to 100 μm, and even more preferably 2 μm to 50 μm.

[0073] In one embodiment, the transmittance of the substrate at a wavelength of 1032 nm is 60% to 95%, preferably 70% to 90%.

[0074] In one embodiment, the transmittance of light of a wavelength of 355 nm of the substrate is preferably 50% or less, more preferably 0% to 20%.

[0075] The tensile modulus of the substrate at 200°C is preferably 5 MPa to 2 GPa, more preferably 10 MPa to 1.8 GPa, further preferably 500 MPa to 1.8 GPa, and particularly preferably 1 GPa to 1.5 GPa. If within such a range, the gas generated by thermal decomposition of the photothermal conversion layer by laser irradiation is preferably blocked by the substrate, and preferably exhibits peelability caused by the shape change of the surface of the photothermal conversion layer. The tensile modulus can be measured using a dynamic viscoelasticity measuring device. The specific measurement method is described below.

[0076] The 5% weight loss temperature of the above-mentioned substrate after ultraviolet irradiation is preferably above 300°C, more preferably 350°C to 650°C, further preferably 380°C to 600°C, and particularly preferably 400°C to 590°C. If it is within this range, an adhesive / adhesive sheet with excellent heat resistance can be obtained. In addition, the RDL formation process is usually carried out at a temperature below 250°C, so if the 5% weight loss temperature after ultraviolet irradiation is within the above range, the outgassing from the substrate in the RDL formation process is reduced, which can reduce the impact on electronic components and achieve a stable process.

[0077] D. Adhesive layer

[0078] The adhesive layer may include any appropriate adhesive, such as a pressure-sensitive adhesive or a curable adhesive. As the curable adhesive, the active energy ray-curable resin composition may be used.

[0079] Examples of the adhesive include acrylic adhesives, silicone adhesives, epoxy adhesives, styrene thermoplastic elastomers, and ester adhesives. In one embodiment, an acrylic adhesive is used. Examples of the acrylic adhesive are described below.

[0080] (Base polymer)

[0081] Examples of the acrylic pressure-sensitive adhesive include those using, as a base polymer, an acrylic polymer (homopolymer or copolymer) using one or more kinds of (meth)acrylic acid alkyl esters as monomer components. Specific examples of the alkyl (meth)acrylate include C1-20 alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among them, it is preferable to use an alkyl (meth)acrylate having a linear or branched alkyl group having 4 to 18 carbon atoms. In the acrylic polymer, the content ratio of the structural unit of the alkyl (meth)acrylate is preferably 70 to 100 parts by weight, more preferably 75 to 99.9 parts by weight, and further preferably 80 to 99.9 parts by weight, based on 100 parts by weight of the acrylic polymer.

[0082] The acrylic polymer may contain a structural unit derived from another monomer copolymerizable with the (meth)acrylic acid alkyl ester as required in order to improve cohesive force, heat resistance, crosslinking property, etc., to enhance dimensional stability of the adhesive layer, etc. Examples of such monomers include the following monomers.

[0083] Carboxyl-containing monomers: such as ethylenically unsaturated monocarboxylic acids such as acrylic acid (AA), methacrylic acid (MAA), and crotonic acid; ethylenically unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and citraconic acid, and their anhydrides (maleic anhydride, itaconic anhydride, etc.);

[0084] Hydroxyl-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, etc.; unsaturated alcohols such as vinyl alcohol and allyl alcohol; ether compounds such as 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether;

[0085] Amino-containing monomers: such as aminoethyl (meth)acrylate, N, N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate;

[0086] Epoxy-containing monomers: such as glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, allyl glycidyl ether;

[0087] Cyano-containing monomers: such as acrylonitrile and methacrylonitrile;

[0088] Ketone-containing monomers: for example, diacetone (meth) acrylamide, diacetone (meth) acrylate, vinyl methyl ketone, vinyl ethyl ketone, allyl acetoacetate, vinyl acetoacetate;

[0089] Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyl oxazole, N-vinylmorpholine, N-vinylcaprolactam, N-(meth)acryloylmorpholine;

[0090] Alkoxysilyl-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane;

[0091] Isocyanate-containing monomers: (meth)acryloyl isocyanate, 2-(meth)acryloyloxyethyl isocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate.

[0092] These monomers can be used alone or in combination of two or more.

[0093] The weight average molecular weight of the acrylic polymer is preferably 600,000 to 1,600,000, and more preferably 800,000 to 1,500,000. Within this range, an adhesive layer having excellent heat resistance and dimensional stability at high temperatures and suppressing outgassing caused by heating can be formed. The weight average molecular weight can be measured by GPC (solvent: THF).

[0094] (additive)

[0095] The acrylic adhesive may contain any appropriate additives as required. Examples of the additives include crosslinking agents, crosslinking catalysts, tackifiers, plasticizers, pigments, dyes, fillers, anti-aging agents, conductive materials, antistatic agents, ultraviolet light absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, and the like.

[0096] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, Oxazoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc. Among them, epoxy crosslinking agents or isocyanate crosslinking agents are preferred.

[0097] In one embodiment, a heat-resistant adhesive is used as the adhesive contained in the adhesive layer. In this specification, the heat-resistant adhesive refers to an adhesive having a predetermined adhesive force under an environment of 260° C. The heat-resistant adhesive is preferably capable of being used without adhesive residue under an environment of 260° C. The heat-resistant adhesive preferably contains an acrylic resin, a silicone resin, or the like as a base polymer.

[0098] The thickness of the adhesive layer is preferably 5 μm to 100 μm, more preferably 10 μm to 50 μm.

[0099] The transmittance of the adhesive layer at a wavelength of 1032 nm is preferably 75% or more, more preferably 85% or more, and further preferably 90% or more. The upper limit of the transmittance at a wavelength of 1032 nm is, for example, 97% (preferably 98%).

[0100] The transmittance of the pressure-sensitive adhesive layer at a wavelength of 355 nm is preferably 75% or more, more preferably 85% or more, and even more preferably 90% or more. The upper limit of the transmittance at a wavelength of 355 nm is, for example, 97% (preferably 98%).

[0101] E. Method for manufacturing adhesive / adhesive sheet for temporary fixing of electronic components

[0102] The adhesive / adhesive sheet for temporary fixing of electronic components can be manufactured by any appropriate method. The manufacturing method of the adhesive / adhesive sheet for temporary fixing of electronic components includes, for example, the following steps: step (A), preparing a composition for forming a light-to-heat conversion layer; step (B), coating the composition for forming a light-to-heat conversion layer on a support; and step (C), curing the coating layer of the composition for forming a light-to-heat conversion layer. The support may be a substrate constituting the adhesive / adhesive sheet.

[0103] The composition for forming a light-to-heat conversion layer contains carbon black. In one embodiment, the composition for forming a light-to-heat conversion layer may be the curable resin composition (preferably the active energy ray-curable resin composition) containing the carbon black.

[0104] Any appropriate method may be used as a coating method for the composition for forming a light-to-heat conversion layer. Examples of coating methods for the composition for forming a light-to-heat conversion layer include bar coater coating, air knife coating, gravure coating, gravure reverse coating, reverse roll coating, die lip coating, die coating, dip coating, offset printing, flexographic printing, screen printing, and the like.

[0105] When the composition for forming a light-to-heat conversion layer contains an active energy ray-reactive compound, in step (C), the coating layer of the composition for forming a light-to-heat conversion layer is irradiated with active energy rays such as ultraviolet rays. The irradiation conditions can be set to any appropriate conditions depending on the composition of the composition for forming a light-to-heat conversion layer.

[0106] When the composition for forming a light-to-heat conversion layer is thermosetting, a heat treatment is performed in step (C). The heating conditions can be set to any appropriate conditions according to the composition of the composition for forming a light-to-heat conversion layer.

[0107] Example

[0108] The present invention will be described in detail below by way of examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. In addition, in the examples, "parts" and "%" are by weight unless otherwise specified.

[0109] [evaluate]

[0110] (1) Tensile elastic modulus

[0111] The elastic modulus was measured under the following conditions using a dynamic viscoelasticity measuring device (manufactured by TA Instrument, trade name "RSA-3"). For the substrate, the tensile elastic modulus was measured at 200°C. For the photothermal conversion layer, the photothermal modulus was measured after irradiation with ultraviolet light (specific wavelength: 365 nm, cumulative light intensity: 1380 mJ / cm) once with a high-pressure mercury lamp. 2 ) at 25°C after annealing.

[0112] Measuring frequency: 1Hz

[0113] Strain: 0.05%

[0114] Distance between chucks: 20mm

[0115] Sample width: 10mm

[0116] The heating rate from 0°C to 250°C is 5°C / min

[0117] (2) Elastic modulus of the photothermal conversion layer after ultraviolet irradiation using the nanoindentation method

[0118] The pressure-sensitive adhesive sheets obtained in the examples and comparative examples were irradiated once with ultraviolet light (specific wavelength: 365 nm, cumulative light intensity: 1380 mJ / cm 2 ) was used as an evaluation sample.

[0119] The elastic modulus of this sample was measured using a nanoindenter (Triboindenter TI-950 manufactured by Hysitron) by a single indentation method at a predetermined temperature (25° C.) under measurement conditions of an indentation speed of about 500 nm / sec, a pull-out speed of about 500 nm / sec, and an indentation depth of about 100 nm.

[0120] (3) 5% weight loss temperature of substrate and light-to-heat conversion layer after ultraviolet irradiation

[0121] The pressure-sensitive adhesive sheets obtained in the examples and comparative examples were irradiated once with ultraviolet light (specific wavelength: 365 nm, cumulative light intensity: 1380 mJ / cm 2 ) were used as evaluation samples.

[0122] A differential thermal analyzer (manufactured by TA Instruments, trade name "Discovery TGA") was used, with the temperature set to 10°C / min, N2 atmosphere, and flow rate set to 25 ml / min, to measure the temperature at which the weight of a given sample decreased by 5% relative to the dry weight of the sample before the temperature increase. The dry weight of the sample refers to the weight excluding the water in the sample.

[0123] Specifically, about 0.01 g of the evaluation sample is placed in the analysis device, and the temperature is first raised from 20°C to 110°C at the above-mentioned heating rate, and then lowered from 110°C to 20°C at a cooling rate of 10°C / min to remove the influence of the contained water and obtain the dry weight. The temperature is again raised from 20°C to 500°C at the above-mentioned heating rate, and the weight loss of the evaluation sample is measured. The temperature at which the weight loss is 5% is extracted from the obtained data.

[0124] (4) Light transmittance of substrate, light-to-heat conversion layer, and adhesive / adhesive sheet

[0125] The spectrophotometer (trade name "UV-VIS UV Visible Spectrophotometer SolidSpec 3700", manufactured by Shimadzu Corporation) was set up to allow incident light to be incident vertically on each sample, and the transmittance in the wavelength range of 300nm to 2500nm was measured. The transmittance at wavelengths of 355nm and 1032nm was extracted from the obtained transmission spectrum.

[0126] (5) Adhesive layer side adhesion

[0127] The light-to-heat conversion layer side of the adhesive / adhesive sheet was adhered and fixed to a stainless steel plate, and the adhesive layer was adhered to a polyethylene terephthalate film (manufactured by Toray Industries, Ltd., trade name "Lumirror S10", thickness: 25 μm), and the adhesion of the adhesive layer side to PET#25 was measured using a method based on JIS Z 0237:2000 (lamination conditions: 2 kg roller reciprocating once, pulling speed: 300 mm / min, peeling angle 180°, measurement temperature: 23°C).

[0128] (6) Initial (normal) adhesion to glass (light-to-heat conversion layer side)

[0129] The light-to-heat conversion layer side of the adhesive / adhesive sheet was attached to glass, and the initial adhesion of the light-to-heat conversion layer side of the adhesive / adhesive sheet to the glass was measured using a method based on JIS Z 0237:2000 (lamination conditions: 2 kg roller reciprocated once, pulling speed: 300 mm / min, peeling angle 180°, measuring temperature: 23°C). As the above glass and the glass in the following evaluation (7), the non-tin surface of a slide glass manufactured by Matsunami Glass, product number S200423 (water-grinded 65 mm×165 mm×1.3 mmT) was used. The non-tin surface was identified as the surface that did not develop color by UV irradiation using a UV lamp.

[0130] (7) Adhesion to glass after ultraviolet irradiation (photothermal conversion layer side)

[0131] The photothermal conversion layer side of the adhesive / adhesive sheet was attached to glass, and ultraviolet rays (specific wavelength: 365 nm, cumulative light intensity: 1380 mJ / cm) from a high-pressure mercury lamp were irradiated onto the entire surface of the photothermal conversion layer from the glass side using an ultraviolet irradiation device (manufactured by Nitto Seiki Co., Ltd., trade name "UM-810"). 2 Then, the adhesive strength to glass after ultraviolet irradiation was measured by a method in accordance with JIS Z 0237:2000 (lamination conditions: 2 kg roller reciprocated once, pulling speed: 300 mm / min, peeling angle 180°, measurement temperature: 23°C).

[0132] (8) Laser debonding evaluation

[0133] · Evaluation of laser debonding using IR laser

[0134] The adhesive layer (thickness: 10 μm) of the adhesive / adhesive sheet is adhered to a thin glass (cover glass, rectangular No. 1, product name "C050701" manufactured by Matsunami Glass) with a width of 50 mm, a length of 70 mm, and a thickness of 0.12 mmt, which simulates a processed object such as a semiconductor wafer, using a hand roller. The adhesive / adhesive sheet is cut according to the size of the thin glass, and then the photothermal conversion layer is laminated on a support (thick glass (large slide glass, standard large white-edge grind No. 2, product name "S9112" manufactured by Matsunami Glass) with a width of 52 mm, a length of 76 mm, and a thickness of 1.0 mmt, which simulates a light-transmitting support substrate) using a hand roller. The laminate was then placed in an autoclave for heating and degassing (40°C, 5 kgf, 10 minutes) to remove bubbles trapped in the laminate. Then, ultraviolet rays (specific wavelength: 365 nm, cumulative light intensity: 1380 mJ / cm) from a high-pressure mercury lamp were irradiated onto the entire surface of the photothermal conversion layer from the thick glass side using an ultraviolet irradiation device (manufactured by Nitto Seiki Co., Ltd., trade name "UM-810"). 2 ), thereby producing a laminate sample.

[0135] The prepared laminated body sample was irradiated with laser from the support side, and the laser debonding property was evaluated. Specifically, a laser with a wavelength of 1032nm and a beam diameter of about 200μmφ was used, and pulse scanning was performed at an interval of about 60μm in the vertical and horizontal directions under the conditions of output power 5.6W and frequency 25kHz. After the laminated body sample was irradiated with laser, the bonding property was evaluated by the following benchmarks.

[0136] Regarding the evaluation of laser debonding properties, in the debonding operation of thin glass and thick glass, the level at which debonding can be easily performed when one point of the outer periphery of the laminated body sample is lifted up by a cutting knife is evaluated as qualified debonding operation performance (○), the level at which debonding can be finally performed after the entire outer periphery is lifted up by a cutting knife is evaluated as △, and the level at which debonding cannot be performed even if the cutting knife is inserted into the outer periphery and the thin glass (processed body) is broken is evaluated as unqualified (×).

[0137] · Laser debonding evaluation using UV laser

[0138] A laminate sample was obtained in the same manner as in the above-mentioned “Evaluation of laser debonding properties using IR laser”.

[0139] The prepared laminate sample was irradiated with laser from the support side to evaluate the laser debonding property. Specifically, a laser with a wavelength of 355 nm and a beam diameter of about 100 μm was used to perform pulse scanning at an interval of about 60 μm in length and width under the conditions of an output power of 3.0 W and a frequency of 25 kHz.

[0140] (9) Chemical resistance

[0141] The photothermal conversion layer side of the adhesive / adhesive sheet was attached to a support (thick glass (large slide glass manufactured by Matsunami Glass, standard large white-edge grinding No. 2, trade name "S9112") with a width of 52 mm, a length of 76 mm, and a thickness of 1.0 mmt, which simulates a light-transmitting support substrate) using a manual roller, and the entire surface of the photothermal conversion layer side was irradiated with ultraviolet rays (specific wavelength: 365 nm, cumulative light intensity: 1380 mJ / cm) from a high-pressure mercury lamp using an ultraviolet irradiation device (manufactured by Nitto Seiki Co., Ltd., trade name "UM-810") from the glass side. 2 ). The pasted samples were immersed in three polar solvents, namely N-methyl-2-pyrrolidone (manufactured by Kishida Chemical Co., Ltd.), propylene glycol monomethyl ether acetate (manufactured by Tokyo Chemical Industry Co., Ltd.), and dimethyl sulfoxide (manufactured by Tokyo Chemical Industry Co., Ltd.), respectively. Then, the samples were placed at 25°C for 15 minutes, and then the various polar solvents were wiped off and the appearance of the samples was observed. The level of no change in appearance after immersion was evaluated as qualified chemical liquid resistance (○), and the level of fading, swelling, peeling, etc. of the light-to-heat conversion layer observed after immersion was evaluated as unqualified chemical liquid resistance (×).

[0142] [Manufacturing Example 1] Composition A for forming a light-to-heat conversion layer

[0143] 30 parts by weight of 2-ethylhexyl acrylate, 70 parts by weight of methyl acrylate, 10 parts by weight of acrylic acid and 0.2 parts by weight of benzoyl peroxide as a polymerization initiator were added to ethyl acetate, and then heated to 70° C. to obtain an ethyl acetate solution of an acrylic polymer (polymer A).

[0144] An ethyl acetate solution of polymer A (polymer A: 100 parts by weight), 200 parts by weight of an active energy ray-curable oligomer (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "Ultraviolet UV-1700B"), 0.3 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), 1.5 parts by weight of a polymerization initiator (manufactured by BASF, trade name "Omnirad 127D"), and 30 parts by weight of carbon black (manufactured by Dainichi Seika Industries, Ltd., trade name "DYMIC SZ 7740 black") were mixed to prepare a composition A for forming a light-to-heat conversion layer. The composition of the composition A for forming a light-to-heat conversion layer is shown in Table 1.

[0145] [Table 1]

[0146]

[0147] [Manufacturing Examples 2 to 4] Compositions B to D for forming a light-to-heat conversion layer

[0148] Light-to-heat conversion layer-forming compositions B to D were prepared in the same manner as in Production Example 1, except that the amounts of active energy ray-curable oligomer, epoxy crosslinking agent, polymerization initiator, and carbon black were adjusted as shown in Table 1.

[0149] [Manufacturing Example 5] Composition E for forming a light-to-heat conversion layer

[0150] 50 parts by weight of butyl acrylate, 50 parts by weight of ethyl acrylate, 5 parts by weight of acrylic acid, 0.1 parts by weight of 2-hydroxyethyl acrylate, 0.3 parts by weight of trimethylolpropane triacrylate (TMPTA) and 0.1 parts by weight of benzoyl peroxide as a polymerization initiator were added to toluene, and then heated to 70° C. to obtain a toluene solution of an acrylic polymer (polymer B).

[0151] A toluene solution of polymer B (polymer B: 100 parts by weight), 30 parts by weight of an active energy ray-curable oligomer (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "Ultraviolet UV-1700B"), 1 part by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), 1.5 parts by weight of a polymerization initiator (manufactured by BASF, trade name "Omnirad 127D"), and 15 parts by weight of carbon black (manufactured by Dainichi Seika Industries, Ltd., trade name "DYMIC SZ 7740 black") were mixed to prepare a composition E for forming a light-to-heat conversion layer. The composition of the composition E for forming a light-to-heat conversion layer is shown in Table 1.

[0152] [Manufacturing Example 6] Composition F for forming a light-to-heat conversion layer

[0153] 100 parts by weight of maleic acid-modified styrene-ethylene-butylene-styrene block copolymer (SEBS: styrene part / ethylene-butylene part (weight ratio) = 30 / 70, acid value: 10 (mg-CH3ONa / g), manufactured by Asahi Kasei Chemicals Corporation, trade name "Tuftec M1913"), 3 parts by weight of epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD-C"), 5 parts by weight of carbon black (manufactured by Dainichi Seika Industries, Ltd., trade name "DYMIC SZ 7740black"), and toluene as a solvent were mixed to prepare a composition F for forming a light-to-heat conversion layer. The composition of the composition F for forming a light-to-heat conversion layer is shown in Table 1.

[0154] [Manufacturing Example 7] Composition G for forming a light-to-heat conversion layer

[0155] A toluene solution of polymer B (polymer B: 100 parts by weight), 5 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), and 5 parts by weight of carbon black (manufactured by Dainichi Seika Industries, Ltd., trade name "DYMIC SZ 7740 black") were mixed to prepare a photothermal conversion layer-forming composition G. The composition of the photothermal conversion layer-forming composition G is shown in Table 1.

[0156] [Manufacturing Example 8] Composition H for forming a light-to-heat conversion layer

[0157] A toluene solution of polymer B (polymer B: 100 parts by weight), 1 part by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), and 5 parts by weight of carbon black (manufactured by Dainichi Seika Industries, Ltd., trade name "DYMIC SZ 7740 black") were mixed to prepare a photothermal conversion layer-forming composition H. The composition of the photothermal conversion layer-forming composition H is shown in Table 1.

[0158] [Manufacturing Example 9] Resin Layer Forming Composition i

[0159] A resin layer-forming composition i was prepared in the same manner as in Production Example 2 except that carbon black was not added.

[0160] [Manufacturing Example 10] Preparation of Adhesive A

[0161] 95 parts by weight of 2-ethylhexyl acrylate, 5 parts by weight of acrylic acid, and 0.15 parts by weight of benzoyl peroxide as a polymerization initiator were added to ethyl acetate, and then heated to 70° C. to obtain an ethyl acetate solution of an acrylic polymer (polymer C).

[0162] Adhesive A was prepared by mixing an ethyl acetate solution of the polymer C (polymer C: 100 parts by weight) and 2 parts by weight of an epoxy crosslinking agent (trade name “TETRAD-C” manufactured by Mitsubishi Gas Chemical Co., Ltd.).

[0163] [Example 1]

[0164] The photothermal conversion layer forming composition A obtained in Manufacturing Example 1 was applied to a polyethylene terephthalate film (thickness: 75 μm) with a silicone release agent treated surface in a manner such that the thickness after solvent volatilization (drying) was 10 μm, and then dried to form a photothermal conversion layer on the polyethylene terephthalate film, and a polyethylene terephthalate film (manufactured by Toray Industries, Ltd., trade name "Cerapeel", thickness: 38 μm) with a silicone release agent treated surface was laminated between rollers. In this way, an adhesive / adhesive sheet (photothermal conversion layer) sandwiched between polyethylene terephthalate films with silicone release agent treated surfaces was obtained. The obtained adhesive / adhesive sheet was provided for the above evaluation. The results are shown in Table 3.

[0165] [Example 2]

[0166] The adhesive A obtained in Manufacturing Example 10 was applied to one side of a polyimide film (manufactured by DuPont Toray Industries, trade name "Kapton 100H", thickness: 25 μm) in a manner such that the thickness after solvent volatilization (drying) was 10 μm, and then dried to form an adhesive layer on the polyimide film, and a polyethylene terephthalate film (manufactured by Toray Industries, trade name "Cerapeel", thickness: 38 μm) with a silicone release agent treated surface was laminated between rolls to obtain a laminate (adhesive layer / substrate (polyimide film)). The properties of the substrate used are shown in Table 2.

[0167] The photothermal conversion layer-forming composition A obtained in Manufacturing Example 1 was applied to the surface of the substrate opposite to the adhesive layer in a manner such that the thickness after solvent volatilization (drying) was 10 μm, and then dried to form a photothermal conversion layer on the polyimide film, and a polyethylene terephthalate film (manufactured by Toray Industries, Ltd., trade name "Cerapeel", thickness: 38 μm) with a silicone release agent-treated surface was laminated between rollers to obtain an adhesive / adhesive sheet (adhesive layer / substrate / photothermal conversion layer). The obtained adhesive / adhesive sheet was subjected to the above evaluation. The results are shown in Table 3.

[0168] [Table 2]

[0169]

[0170] [Examples 3 to 5, 7 to 10; Comparative Example 1]

[0171] The same operation as in Example 2 was performed except that the photothermal conversion layer-forming composition or the resin layer-forming composition shown in Table 3 was used instead of the photothermal conversion layer-forming composition A to obtain a pressure-sensitive adhesive sheet. The obtained pressure-sensitive adhesive sheet was subjected to the above evaluation. The results are shown in Table 3.

[0172] [Example 6]

[0173] A pressure-sensitive adhesive sheet was obtained in the same manner as in Example 2 except that a PET film (manufactured by Toray Industries, Ltd., trade name "Lumirror S27", thickness: 38 μm) was used instead of a polyimide film (manufactured by DuPont Toray Industries, Ltd., trade name "Kapton 100H", thickness: 25 μm). The pressure-sensitive adhesive sheet obtained was subjected to the above evaluation. The results are shown in Table 3.

[0174] [Comparative Example 2]

[0175] A pressure-sensitive adhesive sheet was obtained in the same manner as in Comparative Example 1 except that a PET film (manufactured by Toray Industries, Ltd., trade name "Lumirror S27", thickness: 38 μm) was used instead of a polyimide film (manufactured by DuPont Toray Industries, Ltd., trade name "Kapton 100H", thickness: 25 μm). The pressure-sensitive adhesive sheet obtained was subjected to the above evaluation. The results are shown in Table 3.

[0176] [Comparative Example 3]

[0177] Composition C3 for forming a light-to-heat conversion layer was prepared by mixing 100 parts by weight of a carbon black-based black printing ink NB300 (manufactured by Dainichi Seika Co., Ltd.) and 5 parts by weight of an isocyanate curing agent (manufactured by Dainichi Seika Co., Ltd., trade name "Lamic B Hardener"). It should be noted that NB300 contains a polyurethane-based vinyl acetate-vinyl chloride copolymer as a binder resin, and an intensity peak believed to be urethane was confirmed by IR.

[0178] The composition for forming a light-to-heat conversion layer C3 was applied to one side of a polyethylene terephthalate film (manufactured by Toray Industries, Ltd., trade name "Lumirror S105", thickness: 25 μm) using a gravure coater so that the thickness after solvent volatilization (drying) was 0.2 μm, and then dried to obtain a laminate C3 (light-to-heat conversion layer / substrate (polyethylene terephthalate film)).

[0179] The adhesive A obtained in Manufacturing Example 10 is applied to the substrate side of the laminate C3 in a manner to have a thickness of 10 μm after the solvent is volatilized (dried), and then dried to form an adhesive layer on the polyethylene terephthalate film, and a polyethylene terephthalate film with a silicone release agent-treated surface (manufactured by Toray Industries, Ltd., trade name "Cerapeel", thickness: 38 μm) is adhered by lamination between rollers to obtain a laminate (adhesive layer / substrate (polyethylene terephthalate film) / photothermal conversion layer).

[0180] The resin layer forming composition i obtained in Manufacturing Example 9 was applied to the surface of the laminate on the side opposite to the adhesive layer in a manner such that the thickness after the solvent volatilization (drying) was 10 μm, and then dried to form a resin layer on the polyethylene terephthalate film, and a polyethylene terephthalate film with a silicone release agent treated surface (manufactured by Toray Industries, Ltd., trade name "Cerapeel", thickness: 38 μm) was laminated between rollers to obtain an adhesive / adhesive sheet (adhesive layer / substrate / photothermal conversion layer / resin layer). The obtained adhesive / adhesive sheet was subjected to the above evaluation. The results are shown in Table 3.

[0181] [Comparative Example 4]

[0182] Composition C4 for forming a light-to-heat conversion layer was prepared by mixing 100 parts by weight of a carbon black-based black printing ink CVL-PR (manufactured by DIC Corporation) with 4 parts by weight of an isocyanate curing agent (manufactured by DIC Corporation, trade name "CVL Hardener No. 10"). It should be noted that CVL-PR contains a polyurethane-based vinyl acetate-vinyl chloride copolymer as a binder resin, and an intensity peak believed to be a urethane was confirmed by IR.

[0183] The composition for forming a light-to-heat conversion layer C4 was applied to one side of a polyethylene terephthalate film (manufactured by Toray Industries, Ltd., trade name "Lumirror S105", thickness: 25 μm) using a gravure coater so that the thickness after solvent volatilization (drying) was 3 μm, and then dried to obtain a laminate C4 (light-to-heat conversion layer / substrate (polyethylene terephthalate film)).

[0184] A pressure-sensitive adhesive sheet was obtained in the same manner as in Comparative Example 3 except that the pressure-sensitive adhesive sheet C4 was used instead of the pressure-sensitive adhesive sheet C3. The pressure-sensitive adhesive sheet was subjected to the above-mentioned evaluation. The results are shown in Table 3.

[0185] [Table 3]

[0186]

[0187]

[0188]

[0189] Description of symbols

[0190] 10. Light-to-heat conversion layer

[0191] 20 Substrate

[0192] 30 Adhesive layer

[0193] 110, 110', 110" Adhesive / Adhesive Sheets for Temporary Fixing of Electronic Components

Claims

1. An adhesive / adhesive sheet for fixing electronic components, the adhesive / adhesive sheet for fixing electronic components comprising a light-to-heat conversion layer, wherein: The transmittance of the adhesive / adhesive sheet for fixing electronic components at a wavelength of 1032 nm is 60% or less. The transmittance of the adhesive / adhesive sheet for fixing electronic components at a wavelength of 355 nm is 60% or less. The light-to-heat conversion layer contains carbon black. The 5% weight loss temperature of the light-to-heat conversion layer after ultraviolet irradiation is 300° C. or higher.

2. The adhesive / adhesive sheet for fixing electronic components according to claim 1, wherein: The light-to-heat conversion layer is composed of a curable resin composition.

3. The adhesive / adhesive sheet for fixing electronic components according to claim 2, wherein: The light-to-heat conversion layer includes a photopolymerization initiator.

4. The adhesive / adhesive sheet for fixing electronic components according to claim 3, wherein: The curable resin composition includes a pentaerythritol-based multifunctional (meth)acrylate.

5. The adhesive / adhesive sheet for fixing electronic components according to claim 1, wherein The light-to-heat conversion layer includes a styrene-based thermoplastic elastomer.

6. The adhesive / adhesive sheet for fixing electronic components according to claim 1, wherein The adhesive / adhesive sheet for fixing electronic components further comprises a substrate, The light-to-heat conversion layer is disposed on at least one side of the substrate.